Green consumers and their identities: how identities change the motivation for green consumption. (12th April 2016) - Costa Pinto, Diego; Nique, Walter Meucci; Maurer Herter, Marcia; Borges, Adilson
Abstract: This research aims to fill the gap in green consumption literature from the perspective of values as types of intentions and identity‐based motivation. In two studies, we examine how the salience of personal and social identities can change the relationship between types of intentions and green consumption. The results demonstrate that when personal identity is salient, self‐transcendence intentions influence green consumption more than self‐enhancement intentions. This is because personal identity (compared with social identity) increases the positive effect of congruent intentions (self‐transcendence) on green consumption. However, when social identity is salient, self‐transcendence and self‐enhancement intentions have a similar impact on green consumption. This is because social identity (compared with personal identity) reduces the negative effect of self‐enhancement intentions on green consumption. Finally, we discuss theoretical and managerial implications for values as types of intentions, identity‐based motivation and green consumption.